Preparation and Adsorption Properties of Bentonite Composite Flocculant - Sun, Hong; He, Jie; Ding, Ming; Shao, Guoquan; Hu, Kunhong (Asian Journal of Chemistry, 2014)
In this paper, by using the orthogonal analysis method, by simulating the adsorption performance of various pollutants in industrial wastewater, to ascertain the optimum process conditions on sodium bentonite modified by cetyltrimethyl ammonium bromide (CTMAB). Based on this technology, prepare cationic polyacrylamide (CPAM) organic intercalation of bentonite and Ni/Si-CTMAB inorganic organic pillared bentonite and got the optimal experiment preparation scheme as well.